Randomised clinical trial: Safety, tolerability, pharmacodynamics and pharmacokinetics of zastaprazan (JP‐1366), a novel potassium‐competitive acid blocker, in healthy subjects. Issue 7 (2nd February 2023) - Hwang, Inyoung; Ji, Sang Chun; Oh, Jaeseong; Kim, Hyojin; Cha, Hyunju; Kim, John; Lee, Chang‐Seok; Yu, Kyung‐Sang; Lee, SeungHwan
Summary: Background: Zastaprazan (JP‐1366) is a novel potassium‐competitive acid blocker with favourable preclinical safety and efficacy profile being developed for the treatment of acid‐related diseases. Aims: To investigate the safety, tolerability, pharmacodynamics and pharmacokinetics of zastaprazan. Methods: A randomised, open‐label, placebo‐ and active‐controlled, single and multiple ascending dose clinical trial was conducted in healthy Korean male subjects. Intragatric pH and serum gastrin were measured to assess the pharmacodynamics, while serial blood and urine samples were collected to assess the pharmacokinetics. Pharmacogenomic evaluation was conducted to explore genetic variants, which can affect the pharmacodynamics and pharmacokinetics. Safety and tolerability including hepatotoxicity were evaluated. Results: Suppression of gastric acid secretion increased as the dose of zastaprazan increased. The percentage of time that gastric pH was over 4 (%Time pH >4) with zastaprazan 20 mg (85.19%) and 40 mg (91.84%) were similar to or greater than that with esomeprazole 40 mg (72.06%). Zastaprazan was rapidly absorbed within 2 h and eliminated with a half‐life of 6–10 h. Pharmacogenomic analysis found no genetic variant of drug metabolising enzymes including CYP2C19 or drug transporters associated with the exposure of zastaprazan. Zastaprazan was well tolerated with no clinically significant changes in safety and tolerability assessments. Conclusions: Zastaprazan was safe and well tolerated after a single oral dose up to 60 mg and multiple oral doses up to 40 mg. It also showed rapid, potent suppression of gastric acid secretion. Pharmacodynamic and pharmacokinetic profile of zastaprazan was suitable for treatment of patients with acid‐related diseases. Abstract : Zastaprazan showed rapid, dose‐dependent suppression of gastric acid secretion which was maintained until nighttime.